Methods for injecting sulfur and resulting composition
Patent Information
- Application Number
- JP2024202245
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-05
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025028911000002 
Figure 2025028911000003 
Figure 2025028911000004
Abstract
Description
[Technical field]
[0001] Field The present disclosure relates generally to the field of electrochemical cells. More specifically, the present disclosure relates to a method for producing an electrochemical cell using a carbon material. The present invention relates to a method for condensing sulfur into a gas phase and the resulting compositions therefrom. [Background technology]
[0002] background The disclosures of the publications, patents, and published patent specifications referenced in this application are No. 6,393,962, which is incorporated by reference into this disclosure in order to more fully describe the state of the art to which this disclosure pertains. can be done.
[0003] Microwave irradiation as an energy source for initiating reactions is more effective than conventional heating methods. It has been attracting attention since the mid-1980s, when an increase in reaction rate was observed using the ion exchange reaction. S. A. Galema, Micro See Wave Chemistry, Chemical Society Review, 26, 1997 (Non-Patent Document 1). Since then, microwave irradiation has been used to dramatically reduce processing time as well as increase yield and It has been shown to have a number of advantages, including improved performance. Direct heating of the reactants by wave irradiation provides a more uniform environment in contrast to conventional heating methods. Therefore, this method is especially attractive for scale-up processes. , Y. Sun, Y. Huang, App. Mat and Interfaces, 2013, 5, 1997 (Non-Patent Document 2), and and L. Noerochim, J. Z, Wang, D. Wexxler, Z. Chaao, HK liu, J. of Power Sources , 2013, 228,198 (Non-Patent Document 3).
[0004] Due to the advantages of material processing by microwave irradiation, this method is suitable for use in Li-ion batteries. It has been explored as an efficient means of synthesizing a variety of materials. Luo et al. Encapsulated in an interconnected mesoporous carbon network for use as an anode in a gyroscopic system This paper shows an example of microwave processing for the synthesis of molybdenum oxide nanoparticles. See Luo. More recently, Noerochim et al. have demonstrated a bendable cathode for lithium batteries. 13 shows the microwave synthesis of molybdenum trioxide using a hydrothermal route for use as a catalyst. See L. Noerchim, supra. Gao et al. previously reported the synthesis of LiV3O8 and and Li3V2(PO4)3, and more recently LiNi 0.5 Mn 1.5 They have succeeded in synthesizing O4. As a point of interest, LiNi was prepared via 7 min of microwave irradiation. 0.5 Mn 1.5 O4 is 4 LiNi prepared using the conventional method of heating for 8 hours 0.5 Mn 1.5 At a faster rate than O4 They exhibited favorable growth behavior and better capacity at high current rates. Gao, L. Wang, L. Chen, X. Jiang, J. Pinto, G. Yang, Electrochim. Acta, 2013, 100, 125 (non-patent text See reference 4.
[0005] In addition, microwave irradiation has been shown to be effective for activating carbon for electrochemical capacitor applications. SE Chun, JF Whitacre, J. of Power Source s, 2013, 240,306 (Non-Patent Document 5).
[0006] Among cathode materials for secondary lithium batteries, elemental sulfur has a capacity of 1672 mAhg relative to lithium. -1 This is the theoretical capacity of most commercially available transition metal phosphates and In addition, elemental sulfur is a useful cathode material for secondary lithium batteries. It also offers several other advantages as a fee, notably its low cost and wide availability. Therefore, sulfur has been extensively studied as a cathode material for secondary lithium batteries. and a cathode material for secondary lithium batteries that can be used in electric and hybrid electric vehicles. is considered a promising candidate for
[0007] Despite this promise, the implementation of Li-S secondary battery systems for high power applications remains a challenge. This is problematic for a variety of reasons. For one, sulfur itself has a relatively low electrical conductivity. Therefore, there is an opportunity to fully realize the advantages of sulfur as a cathode material in Li-S secondary battery systems. Methods and materials for providing such communication are desirable.
[0008] Lithium-sulfur (Li-S) cathode materials have long been considered an attractive alternative to current lithium-ion batteries. Although it has a (10x) advantageous specific capacity over Li-S chemistry, it suffers from poor cycle life and discharge The high dielectric constant of sulfur makes it impractical. The sulfide shuttling reaction leads to irreversible material loss in the battery, which is the energy It decreases the storage capacity over time, thus limiting the development of batteries based on Li-S chemistry. The shuttling is a cyclic process where long-chain lithium polysulfides (Li2S n , 2 < n < 8) generated at the cathode during charging dissolve to become the electrolyte and move to the anode by diffusion, where they react with the lithium electrode in a parasitic manner to form lower-order polysulfides, which diffuse back to the sulfur cathode to regenerate higher-order polysulfides. This polysulfide shuttling or dissolution occurs at the expense of available electroactive sulfur species, so the reversibility of sulfur and / or sulfides is widely considered to be the main technical barrier to the commercialization of high-energy Li-S batteries . Another limitation is that elemental sulfur is not a good electrical conductor (electrical conductivity is 5×10 S cm at 25 °C JPEG2025028911000001.jpg3158 ), which limits the rate at which conventional Li-S batteries can be discharged / charged -30 . -1 ) and .
[0009] Therefore, there is still a need for sulfur-containing cathode materials for lithium secondary cells with improved conductivity and cycle life .
Prior Art Documents
Non-Patent Documents
[0010]
Non-Patent Document 1
Non-Patent Document 2
[0011] overview In one aspect of the present disclosure, a method for forming a carbon / sulfur composite is provided comprising the steps of: A method is provided that includes: a) placing a carbon / sulfur mixture in a reaction vessel; b) placing the reaction vessel in a microwave oven; c) exposing the carbon / sulfur mixture to a microwave heat source; d) increasing the temperature of the carbon / sulfur mixture above the melting point of sulfur; and e) Reducing the temperature of the carbon / sulfur mixture below the melting point of sulfur to cause condensation onto the carbon. forming a carbon / sulfur composite having sulfur.
[0012] [Item 1] 1. A method for forming a carbon / sulfur composite, comprising the steps of: a) placing a carbon / sulfur mixture in a reaction vessel; b) placing the reaction vessel in a microwave oven; c) exposing the carbon / sulfur mixture to a microwave heat source; d) increasing the temperature of the carbon / sulfur mixture above the melting point of sulfur; and e) Reducing the temperature of the carbon / sulfur mixture below the melting point of sulfur to condense onto the carbon. forming a carbon / sulfur composite containing the added sulfur. [Item 2] 2. The method of item 1, wherein the carbon / sulfur composite is a carbon electrode of a lithium-sulfur battery. [Item 3] The sulfur in the carbon / sulfur mixture is present in the form of elemental sulfur, sulfides, disulfides, or sulfur-containing compounds. 2. The method of claim 1, [Item 4] 2. The method of claim 1, wherein the carbon in the carbon / sulfur mixture is a carbon-containing material. [Item 5] The carbon in the carbon / sulfur mixture is carbon black, graphite, carbon fiber, carbon Nanotubes, fullerenes, graphene, graphene oxide, activated carbon, pyrolytic carbon, 2. The method of claim 1, wherein the carbon nanotube is a polymer-derived carbon, a polymer-derived carbon, or a combination thereof. [Item 6] 2. The method of claim 1, wherein the carbon / sulfur composite comprises sulfur infused within the pores of the carbon. [Item 7] 2. The method of claim 1, wherein the carbon / sulfur composite comprises sulfur in an amount of 60 wt.% to 95 wt.%. [Item 8] 2. The method of claim 1, wherein the carbon / sulfur composite comprises carbon in an amount of 5 wt.% to 40 wt.%. These and other aspects of the present disclosure will become apparent upon consideration of the following detailed description and appended claims. It will become clear by doing so. [Brief description of the drawings]
[0013] [Figure 1] 1 is a photograph of a pair of sulfur-injected microwave reactors of different sizes. [Diagram 2] 1 is a TGA plot showing 72% sulfur presence in a microwave-implanted carbon / sulfur composite made according to an embodiment. [Diagram 3]1 is an XRD plot showing the high crystallinity of sulfur in microwave-implanted carbon / sulfur composites made according to the examples. [Figure 4] FIG. 4A is a graph of the capacity versus voltage profile, and FIG. 4B is a graph of the cycle life behavior of a carbon / sulfur composite made in accordance with an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Detailed Description Before describing some exemplary embodiments of the present disclosure, the constructional modes described in the following description are It should be understood that the present disclosure is not limited to any particular method or process steps. It is understood that other embodiments are possible and that the present invention can be practiced or carried out in various ways. do.
[0015] In the context of describing the materials and methods discussed herein (particularly in the accompanying claims), in the context of a range of Use of the term and similar references is expressly intended to be construed as being in accordance with the principles of the present invention unless otherwise indicated herein. covers both the singular and the plural, unless the context clearly indicates otherwise. The recitation of ranges of values herein is to be construed as falling within the ranges set forth elsewhere in this specification. Unless otherwise specified, they serve as a shorthand method of referring separately to each individual value that falls within the range. Each individual value is intended to be the same as if it were set forth individually herein. All methods described herein are incorporated herein by reference in their entirety. Unless otherwise indicated or otherwise clearly contradicted by the context, The examples and exemplary language provided herein (e.g., Any use of the phrase "such as" will serve to further clarify the materials and methods of this disclosure. It is intended that the present invention be limited only to the scope of the present application unless otherwise claimed. No language in this specification poses any limitation on the scope of the claimed invention. Any missing element shall not be construed as essential to the practice of the materials and methods of the disclosure. You shouldn't.
[0016] Throughout this specification, the terms "one embodiment," "certain embodiment," and "particular embodiment" are used. "one or more embodiments," or "one A reference to an "embodiment" includes the specific It is intended that a feature, structure, material, or characteristic be included in at least one aspect of the present disclosure. Thus, the phrases "in one or more embodiments" in various places throughout this specification may refer to "in one or more embodiments," "in certain embodi "in one embodiment," "in one embodiment," or "in one aspect" The appearance of phrases such as "in embodiment" do not necessarily refer to the same embodiment of the disclosure. Furthermore, the particular features, structure, materials, or characteristics of the In embodiments, they may be combined in any suitable manner.
[0017] Carbon has a tendency to absorb microwave radiation, even though the polar solvent Even if it is not present, it is converted into heat. HM Kingston, SJ Haswell, Microwave Enhan ced Chemistry:Fundamentals, Sample Preparation and Application, ACS, Washington Therefore, materials with a coating or physical mixture of carbon are conventionally In this regard, the physical Sulfur-implanted carbon composites were successfully synthesized using microwave irradiation of various carbon / sulfur mixtures. Microwave irradiation has been successfully used to fabricate a variety of materials for other battery chemistries. Nevertheless, it has been investigated as a method for producing lithium-sulfur battery materials. It is not thought that this is the case.
[0018] The best conventional method of sulfur injection reported or followed is high temperature 550°C for 4 hours. In addition, additional time is required for heat ramping and cooling of the reaction vessel. Moreover, these conventional methods involve high temperature implantation, This process requires a specially designed pressure vessel. For example, a 0.5 kg scale For a batch of 1000 ml, a traditional process of complete heating and cooling can take up to 16 hours or more. This is a clear barrier to efficient large-scale processing. used microwave radiation to incorporate sulfur into cathode materials for lithium-sulfur battery applications. There are.
[0019] Sulfur condensed onto a carbon host using microwave irradiation results in scalable This process provides improved quality, economic viability, time savings, and efficiency. Microwave irradiation provides faster injection, shorter thermal ramping, increased thermal efficiency, and improved scalability. This offers the advantage of increased product consistency for the roll-up. Materials that involve physical mixing are more effectively processed by microwave irradiation than by conventional methods. In this regard, microwave irradiation of a physical carbon / sulfur mixture was used to The sulfur-injected carbon composite based on the process was successfully synthesized. Microwave irradiation has been shown to be effective in other battery Despite the success of creating a variety of materials for chemical applications, no one has been able to create lithium-sulfur battery materials. It is not believed that this has previously been investigated as a method for producing
[0020] The present disclosure provides, through the use of a microwave source, a carbon cathode for, for example, lithium-sulfur battery applications. One embodiment of the process is a method for condensing sulfur on a carbon material such as a carbon / placing the sulfur mixture in a reaction vessel; placing the reaction vessel in a microwave oven; exposing the carbon / sulfur mixture to a microwave heat source until the carbon / sulfur mixture is heated above the melting point of sulfur; and decreasing the temperature of the carbon / sulfur mixture until it is below the melting point of sulfur. to form a carbon / sulfur complex in which the sulfur is condensed onto the carbon.
[0021] A suitable carbon / sulfur composite contains sulfur in an amount of 60 wt.% to 95 wt.% and carbon in an amount of 5 wt.% to 95 wt.%. Contains 40 wt.%.
[0022] Suitable carbon and carbon-containing materials in the carbon / sulfur mixture include carbon black, graphite, Fite, carbon fiber, carbon nanotube, fullerene, graphene, graphene oxalate Examples of carbon-based materials include carbides, activated carbon, pyrolytic carbon, polymer-derived carbon, and combinations thereof.
[0023] Suitable sulfur and sulfur-containing materials in the carbon / sulfur mixture include elemental sulfur, sulfides, disulfides, and sulfur-containing materials. Rufides, and combinations thereof.
[0024] Suitable equipment for use in the microwave injection reactions of the present disclosure may be any microwave-compatible The reactor may be made of a microwave safe material. Cover made of microwave compatible material including plastic, glass, plastic, or other suitable material. It is a container with a seal.
[0025] In one embodiment, the reactor is a microwaveable vessel with a threaded cover. Even trace amounts of carbon can heat up and react when irradiated with microwaves. Care was taken to clean the reactor threads as this could prevent the reactor from being opened. The microwave reactor containing the carbon / sulfur mixture should be placed in a microwave oven. A conventional microwave oven may be used. In one embodiment, a power of 5 Microwave emission sources of between 00 and 1500 watts are useful for use in the implantation process. In this manner, microwave emission sources with a power of 750 to 1250 watts are useful for use in implantation processes. In some embodiments, a microwave oven with a power of 1000 watts is used for the injection process. may be used for.
[0026] Irradiation of the vessel to condense sulfur onto the carbon material is necessary to complete the injection process. This is done in a time that depends on the power capabilities of the microwave source. For example, the sample It was successfully irradiated at 1000 watts for 35 seconds.
[0027] The injection time was optimized using a conventional glass tube reactor. When irradiated, the temperature rises to a range of several hundred to over 2000°C in a short time, usually a fraction of a second, and then This helps to sublimate the sulfur species. Since the reactor is a closed pressure reactor, the reaction The pressure inside the vessel causes the sulfur vapor to condense onto the carbon. If extended duration injection is desired by simply reducing oven power to 1 / 5 or 1 / 10 based on requirements. It is also possible to increase the injection time by
[0028] In one embodiment, the sulfur is infused into the carbon in the carbon / sulfur composite. In this case, the carbon is a carbon matrix into which sulfur can be incorporated. In one embodiment, the sulfur is infused into the pores of the carbon. In one embodiment, the carbon is a carbon black composite. In the present invention, the carbon is a carbon cathode composite.
[0029] The present disclosure will be further illustrated with reference to the following specific examples. It will be understood that the examples They are offered as examples and are not intended to limit the scope of the disclosure or the appended claims. It hasn't been done yet. EXAMPLES
[0030] To perform microwave implantation of sulfur onto carbon materials, 3 grams of carbon and 7 grams of sulfur were The mixture blended in the desired ratio of 3:7 was placed in a microwave reactor as shown in FIG. The microwave reactor containing the nitrogen / sulfur mixture was placed in a microwave oven.
[0031] Thermogravimetric analysis (TGA) data shown in Figure 2 indicates that 72% of the sulfur was removed from the cathode composite exposed to microwaves. It has been shown that there is a presence of Cr-Si, which is desirable and within the conductive regions of the composite. There is enough in there.
[0032] Figure 3 shows the X-ray diffraction (XRD) of the sulfur carbon composite injected at 100% power for 35 seconds. The peaks in the XRD pattern are the same as those injected using the conventional method. The composite sulfur should be amorphous as seen in the XRD pattern (not shown). However, it shows high crystallinity. This is because the carbon is irradiated with microwaves. This may be due to the high temperature heating process induced by the This behavior is predictable since the reaction transforms amorphous to highly crystalline even when heated.
[0033] 4A and 4B show Li-S batteries assembled using microwave-implanted sulfur carbon composites. The electrochemical charge and discharge behavior of the Li-S battery with the synthesized composite cathode is shown. To investigate the change in chemical properties, a lithium metal anode was used as the counter electrode and the charge was charged at 3.0 to 1.7 C at a rate of 0.5 C. A charge-discharge test was performed at a cell voltage of 100 V.
[0034] FIG. 4A shows a plot of voltage versus capacity for a Li-S battery at room temperature. Reflects the reversible formation of various products in the battery, starting from elemental sulfur to Li2S An initial discharge capacity of 1091 mAh / g was observed along with a discharge / charge plateau. The multiple discharge / charge voltage plateaus were in good agreement with previously reported studies. Even after 240 cycles, no change was observed in the voltage plateau, which indicates that cycling the cell This indicates that increasing the Very preferred for pond applications.
[0035] FIG. 4A shows a typical capacitance vs. voltage profile, and FIG. 4B shows the capacitance vs. voltage profile of the carbon-sulfur composite. The cell was discharged and charged at a rate of 0.5 C, where the capacity is the capacity of sulfur. Reported as a percentage of active mass (72%). Carbon-sulfur complex containing 72% sulfur. The cycle life plot of the 0.5 C discharge / charge cycle is shown in FIG. Strong cycling stability was observed over 10000 cycles. The rate is based on the theoretical capacity of sulfur, which is the percentage of active mass of sulfur present in the complex. The percentage here is 72%. Carbon / sulfur complex The battery maintained a very stable capacity of over 800mAh / g for 240 cycles, and It then dropped to 795mAh / g at the end of 240 cycles.
[0036] Although various aspects have been illustrated and described in detail herein, it will be apparent to one skilled in the art that As an aside, various modifications, additions, and substitutions may be made without departing from the spirit of this disclosure. These may be implemented and are therefore defined in the appended claims. are considered to be within the scope of this disclosure.
Claims
[Claim 1] The invention described in this specification.
Citation Information
Patent Citations
A method for prepare a sulfur-carbon composite cathode material for lithium-sulfur battery
CN109037662A
Sulfur-carbon composite, preparation method therefor, and lithium secondary battery comprising same
WO2019098733A1